1991
DOI: 10.1002/ajmg.1320410108
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of auriculo‐cardiovascular‐skeletal malformations: A new malformation complex in an infant of a diabetic mother?

Abstract: The incidence of malformations among infants of diabetic mothers (IDM) is known to be higher than in the general population. These malformations usually involve several organ systems and in the past few years there has been an attempt to group them into distinct "syndromes." The present report concerns a child with a specific constellation of findings not yet reported in the infant of a diabetic mother, and we urge our colleagues to look for other associations existing in these infants, rather than just listin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Conversely, skeletal, cardiovascular, and genitourinary system malformations, commonly described in infants of diabetic mothers [Berkenstadt et al, 1991], have been seldom observed in patients with hyperinsulinism. None of 17 patients had malformations, but among our large series of 175 hyperinsulinemic patients, 3 had Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, skeletal, cardiovascular, and genitourinary system malformations, commonly described in infants of diabetic mothers [Berkenstadt et al, 1991], have been seldom observed in patients with hyperinsulinism. None of 17 patients had malformations, but among our large series of 175 hyperinsulinemic patients, 3 had Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Additional reports also support these associations. Berkenstadt et al [1991] described an infant of a diabetic mother with bilateral microtia and cardiovascular anomalies, and Ziereisen et al [1997] reported on an infant born to a mother with insulin‐dependent diabetes with micrognathia, femoral hypoplasia (a characteristic finding of infants of diabetic mothers), and congenital heart anomalies. They thought that this infant was similar to that reported by Berkenstadt et al [1991] and that they both could have a diabetic fetopathy.…”
Section: Discussionmentioning
confidence: 99%
“…However, craniofacial anomalies have been described in only a small number of reports [Becerra et al, 1990; Johnson et al, 1983; Ramos‐Arroyo et al, 1992]. Patients have been described with the femoral‐facial syndrome [Daentl et al, 1975; Hurst and Johnson, 1980; Johnson et al, 1983] and auricular abnormalities including microtia and preauricular tags as a consequence of maternal diabetes [Berkenstadt et al, 1991; Johnson and Fineman, 1982; Lin et al, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…Johnson and Fineman 1982 reported on two patients, offspring of diabetic mothers, with bilateral preauricular tags, microtia, and tetralogy of Fallot, truncus arteriosus, and hemivertebrae. Berkenstadt et al 1991 and Ziereisen et al 1997 reported infants of a diabetic mother with ear and congenital heart anomalies. Because our patient had OAVS and CRS together, we hypothesized that the overall patient diagnosis was AMDS.…”
Section: Discussionmentioning
confidence: 99%